Surplus Property Act of 1944 and Amendments. (U.S. Congressional Research., 1973)
Contains text of Surplus Property Act of 1944 and texts or extracts of amending or related public laws, 1944-72, as compiled by Gilman G. Udell, Document Room Superintendent, House of Representatives.